2015
DOI: 10.1208/s12248-015-9719-7
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Proteins and Peptides in the Treatment of Neurodegenerative Diseases

Abstract: Abstract. The blood-brain barrier (BBB) is a major impediment to the therapeutic delivery of peptides and proteins to the brain. Intranasal delivery often provides a non-invasive means to bypass the BBB. Advantages of using intranasal delivery include minimizing exposure to peripheral organs and tissues, thus reducing systemic side effects. It also allows substances that typically have rapid degradation in the blood time to exert their effect. Intranasal delivery provides the ability to target proteins and pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(107 citation statements)
references
References 72 publications
1
97
0
4
Order By: Relevance
“…Intranasal administration is suggested for treatment of neurodegenerative diseases. 23,37 Topical application to skin was used to achieve dermal vasodilation, 38 while buccal delivery for treatment of type 2 diabetes. 39 Topical ocular application of PACAP has already been used to test local, corneal effects of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal administration is suggested for treatment of neurodegenerative diseases. 23,37 Topical application to skin was used to achieve dermal vasodilation, 38 while buccal delivery for treatment of type 2 diabetes. 39 Topical ocular application of PACAP has already been used to test local, corneal effects of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses and bacteria co-opt this olfactory route for brain infection, and more than 40 substances have been shown to enter the brain by this means (93, 94). Viruses, such as Venezuelan equine encephalitis virus, initially infiltrate the CNS via olfactory axons, then induce BBB permeability throughout the brain to promote a second wave of infection, as virion particles enter the brain from the circulation via the damaged barrier (95).…”
Section: Potential Routes Of Antibody Entry Into the Cnsmentioning
confidence: 99%
“…To increase brain targeting, intranasal delivery is an excellent non-invasive form of administration [24]. Banks et al reported that, compared with intravenous administration, intranasal administration of radioactively labeled exendin(9-39), a glucagon-like peptide-1 (GLP-1) receptor antagonist, was four times more effective in delivery to the olfactory bulb, but three times lower in delivery to the rest of the brain [25].…”
Section: Peptide Drug Delivery Is a Key Issuementioning
confidence: 99%